Impact of land-use and flow conditions on the phytoplankton of the Sabie River, South Africa - Barnard, Sandra; Morgenthal, Theunis L.; Stolz, Micaela; Venter, Arthurita (African Biodiversity & Conservation, 2021)
Background: The understanding of the impact of land-use on the dynamics of phytoplankton assemblages during varying climate conditions on rivers is limited. Objective: To determine the impact of land-use types and flow on phytoplankton assemblages in the Sabie River. Methods: The relationships between land-use patterns, water quality and phytoplankton assemblages were analysed using canonical correspondence analyses (CCA). Results: Six main land-use types could be distinguished in the eight identified sub-catchments of the river. The CCA results showed that the land-use had a stronger correlation with phytoplankton classes during the higher flow conditions than during low flow conditions. The forestry land-use type had the strongest correlation with nitrate–nitrite concentrations in the Sabie River. Chlorophyll-a concentrations were higher during 2016, and a slightly lower number of genera were observed for the class Chlorophyceae. During 2017 the number of genera of the class Cyanophyceae decreased together with chlorophyll-a and total cell concentrations. Conclusion: Low flow conditions favoured filamentous genera that are common to mesotrophic conditions while higher flow conditions favoured single-celled small genera more common to oligotrophic waters with higher disturbance. This study showed that flow has the potential to enhance the impact of land-use on phytoplankton community dynamics in a river system and thereby may have further impacts on the health and activities of surrounding communities.